Effects of different inclines on lower limb muscle activation during cycling - Tseng, Y.-H.; Yen, W.-L.; Chen, K.-I.; Wang, H.-H.; Lin, Z.-J.; Lu, C.-Y.; Tasi, W.-C.; Chen, C.-H. (Journal of Science and Cycling, 2025)
This study aimed to examine the effects of different inclines on lower limb muscle activation during cycling. Twelve university students (mean height: 170.6 ± 3.5 cm, mean weight: 67.8 ± 7.1 kg, mean age: 20.5 ± 0.4 years) participated in the study. Muscle activation of the rectus femoris, biceps femoris, tibialis anterior, and gastrocnemius were measured using a DELSYS electromyography (EMG) system. A smart bicycle posture adjustment system was utilized to modify seat tube angles and handlebar positions. Participants completed cycling trials at three incline conditions—flat (0°), uphill (+5°), and downhill (-5°)—while maintaining a workload of 100 W and a cadence of 90 rpm. Repeated measures ANOVA was performed to analyze differences in muscle activation across inclines. The results indicated that rectus femoris, biceps femoris, and gastrocnemius activation was significantly higher during uphill cycling compared to flat and downhill conditions. Additionally, activation of these muscles was greater on flat terrain than during downhill cycling, whereas tibialis anterior activation did not differ significantly across inclines. These findings suggest that even a 5° change in incline alters lower limb muscle activation patterns, providing valuable insights for cycling training and biomechanics research.